Penghapusan Kebijakan Denda Keterlambatan pada Pembiayaan Bermasalah PT Bank BNI Syariah - Laode Arahman Nasir; Wasilah Wasilah (Universitas Agung Podomoro, 2018)
This study aims to analyze the policy of late charge elimination applied to PT Bank BNI Syariah. This policy was initiated at the year of 2016 which predictably lead to the inclination of problematic financing at BNI Syariah. This study provides evaluation and recommendation for policy implementation to reduce the number of problematic financing. This study uses qualitative methods with a case study approach. The research instrument used was through the interview process with BNI Syariah and the DSN (Dewan Syari‟ah Nasional/ Read: National Board of Islamic Law) of MUI (Majelis Ulama Indonesia/ Read: Indonesian Muslim Scholars Council). The results of the study reveals that the application of a fine-elimination policy was applied because of bank doubts about the application of fines to sharia and fines that have no effect on the bank’s income. PT Bank BNI Syariah uses persuasive policies and still applies the ta'widh policy after the application of the fine is eliminated. This policy has a positive impact on marketing but is still vulnerable to an increase in the level of Non Performing Financing (NPF).